QTL mapping and identification of candidate genes using a genome-wide association study for heat tolerance at anthesis in rice (Oryza sativa L.) - Changmin Hu; Changmin Hu; Jianhua Jiang; Yulong Li; Shaojie Song; Yu Zou; Chunyu Jing; Ying Zhang; Dezheng Wang; Qiang He; Xiaojing Dang (Frontiers in Genetics, 2022)
Heat tolerance (HT) of rice at anthesis is a key trait that ensures high and stable yields under heat stress. Finding the quantitative trait loci (QTLs) and gene loci controlling HT is crucial. We used relative spikelet fertility (RSF) as a measure of HT. The phenotypic values of RSF in 173 rice accessions were investigated in two environments and showed abundant variations. We performed a genome-wide association study on RSF using 1.2 million single nucleotide polymorphisms (SNPs). Five QTLs were significantly associated with RSF were identified, four were found in previously reported QTLs/genes, and one was novel. The novel QTL qRSF9.2 was mapped into the 22,059,984-22,259,984 bp region, which had 38 positional candidate genes. By combining the linkage disequilibrium analysis, the QTL region was narrowed to 22,110,508–22,187,677 bp, which contained 16 candidate genes. Among them, only gene LOC_Os09g38500 contained nonsynonymous SNPs that were significantly associated with RSF. In addition, accessions with large and small RSF values had corresponding respective high and low gene expression levels. Furthermore, the RSF of the CC allele was significantly higher than that of the TT allele. Hap 2 and Hap 3 can increase heat tolerance by 7.9 and 11.3%, respectively. Our results provide useful information that recommends further cloning of qRSF9.2 and breeding heat-tolerant rice varieties by marker-assisted selection.